The dominant species of herpetofauna in the coal mining area at East Kalimantan, Indonesia - TEGUH MUSLIM; ULFAH KARMILA SARI; ISHAK YASSIR (Biodiversitas Journal of Biological Diversity, 2017)
Muslim T, Sari UK, Yassir I. 2017. The dominant species of herpetofauna in the coal mining area at East Kalimantan, Indonesia. Biodiversitas 18: 773-779. Changing of habitat condition influences the variety of species including Herpetofauna. Herpetofauna is one of the components in the ecosystem that plays an important role, both from the ecological and economical aspect. From the ecological aspect, it has a specific role in the food chain, and it can also be used as a bio-indicator of the environment’s condition. Furthermore, herpetofauna found in reclamation area of coal mining not only stabilizes the ecosystem in the food chain, but also it can be used as a bioindicator of environment changes and the success rate of reclamation. The aim of this research was to find out the community of herpetofauna comprising and dominating the coal mining reclamation area, especially the wet and dry areas. The research location was located at PT. Singlurus Pratama Kalimantan Timur. The methods used in this research were visual encounter survey and patch sampling. This research found 10 species from 5 families of reptiles and 11 species from 6 families of amphibians. The highest dominant index score for reptile was 0.71, found in the fragmented forests. Meanwhile, the dominant reptile species were Eutropis multifasciata (20 individuals), Enhydris enhydris (4 individuals), and Dendrelaphis pictus (4 individuals). The highest dominant index score for amphibian was 1, found in the settling pond. Moreover, the dominant amphibian species were Polypedates leucomystax (42 individuals) and Fejervarya cancrivora (41 individuals). These two species were the ones able to survive in the degraded areas and they were easily found in the areas with disrupted habitats.